AI in Action: Exploring Practice Teachers' Integration of Artificial Intelligence in Lesson Demonstrations - Pusoc, Jeric; Luague, Nicole; Morata, Jessa; Pedroso, John Erwin (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
Artificial Intelligence (AI) plays a crucial role in our ever-evolving digital world. It benefits 21st-century citizens by offering a wide range of tools that drive technological advancements across various fields, including medicine, science, and, most importantly, the educational landscape. The integration of AI in education supports practice teachers by enabling innovative teaching practices, personalized learning experiences, and data-driven decision-making. Accordingly, this study explored the integration of artificial intelligence into the lesson demonstrations of practice teachers. It is anchored in George Siemens’ Connectivism Theory, which posits that knowledge is distributed across networks and that learning occurs through connections between people, ideas, and resources. Employing a descriptive qualitative approach, the study identified five major themes and fourteen subthemes. Findings conclude that AI serves as a transformative tool that enhances instructional design, classroom engagement, and teacher confidence when thoughtfully integrated into lesson demonstrations. It is recommended that future research involve a larger and more diverse sample and explore broader dimensions of AI in education to deepen understanding and support effective implementation.